Fecundidad de la anchoveta Cetengraulis mysticetus (pisces: engraulidae) en la población de la parte interna del Golfo de Nicoya, Costa Rica (ING) - Ruiz G., Kehrson; Rodríguez M., Jorge Arturo; Soto R., Rosa L. (Uniciencia, 2001)
The anchovy Cetengraulis mysticetus is used as bait by the artisanal fishing fleet. Some reproductive aspects were studied during the spawns of 1997 and 1998. The size of the first maturity for that time was estimated at 14,6 cm and sexual proportion of 1:1.2 (males: females) was found. The fecundity study yielded mature females of sizes between 16.2 and 21.3 cm of total length. Relative fecundity varied from 1,867 eggs per gram of fish in the bigger fish to 921 eggs per gram of fish in the group of smaller size. The relation between number of eggs and fish size yielded a total fecundity of 0.10 * LT4.55 while the relative fecundity was 0.17 * PT1.19 (PT = total weight). The gonadosomatic index was calculated for males and females in different maturity stages. The maximum values were obtained in the stage IV and were bigger in males than in females.